Analisis Pola Komunikasi Interpersonal: Fondasi Pilar Keluarga Sakinah - Susiana, Susiana; Susanti, Neneng Desi (JAWI : Journal of Ahkam Wa Iqtishad, 2023)
This study addresses the issue of interpersonal communication patterns in establishing a harmonious family. Communication is emphasized in the holy Qur'an as a crucial aspect of human life, particularly for Muslims. Poor communication is one of the factors that can lead to marital disharmony or discomfort within the family. Therefore, effective communication is essential for a healthy family life. To achieve a harmonious and content family, it is essential to understand the patterns of interpersonal communication within the family. This will lead to a peaceful and comfortable environment for all members. The authors aim to discuss effective communication techniques, both in general and within a religious context, to establish a happy family. The research focuses on examining theories related to positive communication patterns within the family. The methodology employed for this research is library research. A balanced communication pattern is essential for forming a harmonious family. Additionally, precise subject-specific vocabulary should be used when it conveys the meaning more precisely than a similar non-technical term. This involves open communication where each member has an equal opportunity to express their opinions about family life. It is important to avoid any biased or emotional language and to use clear, objective, and value-neutral language. The text is grammatically correct and follows conventional academic structure and formatting. No changes in content have been made.